Veil, Voice, and Violence: The Portrayal of Muslim Women in Indian Cinema (1992–2002) and a Comparative Analysis of Coverage in the Economic and Political Weekly (Journal of Advances and Scholarly Researches in Allied Education, 2026)
This paper examines the representation of Muslim women characters in mainstream Indian cinema during the decade from 1992 to 2002 — a period bookended by the demolition of the Babri Masjid and the aftermath of the Gujarat pogrom, two events that profoundly reshaped Hindu-Muslim relations and the cultural imagination of India. Drawing on close readings of significant films including Bombay (1995), Mammo (1994), Sardari Begum (1996), Zubeidaa (2001), Fiza (2000), and Lagaan (2001), among others, the paper argues that Indian cinema during this decade oscillated between two dominant archetypes: the tragic Muslim woman sacrificed on the altar of communal harmony, and the doomed Muslim woman whose modernity is punished by her own community. The paper then compares these cinematic representations with the analytical and critical discourse in the Economic and Political Weekly (EPW), which during the same period published significant scholarship on Muslim identity, communalism, gender, and secularism. The comparison reveals a productive but often asymmetrical dialogue between popular cultural production and academic criticism: while EPW scholars interrogated the ideological underpinnings of secularist representations and the politics of Muslim women's rights, Indian cinema continued to deploy Muslim women primarily as emotional and symbolic currency in narratives centred on Hindu-Muslim conflict, national belonging, and masculinist desire. The paper concludes that the decade's cinematic and scholarly production together illuminate the contested terrain of Muslim femininity in post-Babri India.